Calcifying odontogenic cyst mimicking endodontic pathology: a case of unnecessary endodontic treatment of vital teeth - Hosam Zebda; Sarah Obeidat; Amr Abdelmoez; Ali Fahd (BMC Oral Health, 2026)
Abstract Background Calcifying Odontogenic Cyst (COC) is a rare developmental odontogenic lesion that may present as a periapical radiolucency, mimicking inflammatory pathology and posing a diagnostic challenge. Case presentation In this report, a 17-year-old female patient was referred to an oral surgery practice with a history of recurrent swelling and pain in the anterior mandible. Teeth 31, 41, and 42 (according to the FDI International two-digit system) had been endodontically treated by the referring dentist prior to referral. Clinical examination revealed a localized labial swelling without signs of acute infection. A panoramic radiograph provided with the referral demonstrated a well-defined unilocular periapical radiolucency extending across the mandibular incisors. The initial management by the general dental practitioner was based primarily on radiographic findings, without documented pulp vitality testing, leading to root canal treatment of multiple teeth prior to specialist referral. Following referral, an incisional biopsy was performed, and histopathological analysis revealed a cystic lesion lined by ameloblastomatous-type odontogenic epithelium with characteristic ghost cells and calcifications, confirming the diagnosis of a calcifying odontogenic cyst. The lesion was surgically enucleated, and one-year follow-up showed complete healing with no recurrence. Conclusion This case highlights the diagnostic challenges associated with non-endodontic periapical lesions and emphasizes the critical importance of pulp vitality testing, careful radiographic interpretation, and timely specialist referral to avoid unnecessary and irreversible dental treatment.